High-temperature mechanical properties of FeCoCrNi high-entropy alloys fabricated via selective laser melting - Lin, Danyang; Xi, Xin; Li, Xiaojie; Hu, Jixu; Xu, Lianyong; Han, Yongdian; Zhang, Yankun; Zhao, Lei (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2022)
The high-temperature application of high-entropy alloys (HEAs) fabricated via selective laser melting (SLM) relies on an in-depth understanding of the mechanical properties and deformation mechanisms involved. This study conducted tensile testing of FeCoCrNi HEA, at various temperatures and strain rates, where the microstructure was systematically characterized before and after deformation. The FeCoCrNi HEAs fabricated via SLM exhibited a greatly enhanced tensile strength at room temperature compared to those produced by traditional processing, but the strength at high temperature was significantly compromised. Experimental data were used to calculate the parameters of a constitutive model based on three classical mathematical models to predict the flow behavior at elevated temperatures. The softening mechanism was attributed to the evolution of the dislocation network, and a structure–mechanism–property relationship at elevated temperatures was established. Further, cracks initiated at the grain boundaries at elevated temperatures owing to nano-clustering. These results are expected to contribute to the development and improvement of SLM-HEAs for use at high temperatures. •Strengthening of SLM-HEAs is mainly attributed to dislocation networks.•Effect of dislocation networks was compromised at elevated temperatures.•High temperature embrittlement is caused by nano clustering at grain boundaries.•Experimental data were used to model high-temperature tensile strength.